Particularitățile hidrolizei membranare și a absorbției glucidelor în intestinul subțire la șobolanii albi în funcție de stresoreactivitatea constituțională - Grosul-Raileanu, Olesea; Șeptițchi, Vladimir; Leorda, Ana (Editura USM, 2024)
The aim of this work is to clarify the features of membrane hydrolysis of maltose and the absorption of glucose formed during hydrolysis, as well as free glucose and fructose in the small intestine of rats with different levels of constitutional stress reactivity. Significant differences in the intensity of free glucose and fructose absorption, membrane hydrolysis of maltose and absorption of glucose formed during hydrolysis were found in rats with different levels of constitutional stress reactivity. The highest rate of free glucose absorption is observed in animals with an average level of stress reactivity, and fructose - in animals with a low level of reactivity; the lowest rate of free monosaccharide absorption is observed in animals with high stress reactivity. Animals with an average level of constitutional reactivity have a higher intensity of membrane hydrolysis of maltose and glucose formed during hydrolysis compared to animals with high stress reactivity. The obtained data indicate the existence of a connection between the genetically determined stress reactivity of the body and the digestive-transport function of the small intestine.
Keywords: small intestine; membrane hydrolysis of maltose; glucose absorption; fructose absorption; constitutional stress reactivity